Noise Reduction Method of Φ-OTDR System Based on EMD-TFPF Algorithm - Bai, Yu-Xin; Lin, Ting-Ting; Zhong, Zhi-Cheng (IEEE sensors journal, 2021)
The phase-sensitive optical time domain reflectometry ( Φ -OTDR) system has been gradually applied to vertical seismic profile exploration due to its excellent anti-electromagnetic interference, extremely high resolution and sensitivity, and wide detection range. However, the actual data is often disturbed by random noise, which seriously affects the system's ability to recognize low-frequency disturbances. In order to suppress the background noise and improve the signal-to-noise ratio (SNR), a fusion noise reduction method based on empirical mode decomposition and time-frequency peak filtering (EMD-TFPF) algorithm is studied and introduced. In terms of seismic exploration data processing, the algorithm has good denoising performance. Using the Φ -OTDR system based on optical synchronous reference heterodyne detection as the experimental platform, the EMD-TFPF noise reduction algorithm is applied to the position information and compared with the VSS-NLMS, VMD-NWT and EMD-soft methods. Experimental results show that under the conditions of 0.1 Hz and 5 V vibration interference, the EMD-TFPF method improves the SNR to 37.6 dB, which is much higher than the other three noise reduction algorithms. In addition, this method broadens the low-frequency response range of the system to 10 −5 Hz. The improvement of the system's ability to recognize low-frequency disturbance events will undoubtedly accelerate the practical process of the Φ -OTDR system in seismic exploration.